Metrossexualidade e retórica: o homem como produto - Col, Angelo Alecsandro Dal (2010)
The present study analyses the discursive nature of advertising and its implications to the man s changing into an object of consumption as of the appearance of the metrosexual term at advertising. To this analysis, a sample from the magazine Men s Health, that discusses about vanity without, however, designate man as a metrosexual, will be used. To study the discursive advertising aspects, we took as theoretical referential Perelman & Tyteca (2005) and Reboul s (2004) Rhetoric, because of the vast theoretical/methodological display offered by them.To the metrosexuality study, whose creator is the journalist and writer Mark Simpson (1994), we searched many articles, subjects and researches from sites, e-papers and magazines, like Veja, Época and ISTOÉ. Along of the study, many other authors had contributed to our theoretical basis and developed thoughts. The insertion of the metrosexual term at advertising, mainly, happened to persuade contemporary man to consume objects that provides for, above all, his own vanity, a fact that, without changing man in a female, approaches him a lot to significant and characteristic aspects from feminine world. We emphasize an important differential: masculinity is not supported by beauty (as the femininity), but by getting goods and the status which they give to man